Athapascan [Salishan?] village on the Yukon River, Alaska, ca. 1907 - Nowell, Frank H., 1864-1950
Athapascan village on the Yukon River, Alaska, ca. 1907, seen from a distance. In foreground is water, beach with many canoes; in middleground is the village, small houses and tents, and fish racks. Note from unidentified source: A Siwash village on the Yukon